Politične stranke kot predmet politične znanosti - Bibič, Adolf (Teorija in praksa, 1994)
The paper analyses some crucial aspects of contemporary stasiology. Starting from a sketch of the historical dimension of the research of political parties from the beginning of 20th century, the definition of political parties as an instrument of civilized competitive power struggle is underlined. The perception of political parties as a consequence of modern division of civil society and state vis. the central intermediary link between them, the cleavage approach (S. Rokkan-S. M. Lipset) to the genesis, institutionalization aspect of political parties is also considered, deriving new strength from the modern theory of organizations. The typology of parties is seen not a an expression of their static nature but of their historical dynamics. The author agrees with the thesis that the specific function of the parties is to be seen in their competitive struggle for political power, though other kinds of functions of political parties is stressed as well. These and other dimensions of contemporary stasiology have special significance for the analysis of political parties in the period of their transition from the monistic (socialist) political system to pluralistic democracy and its consolidation. Implicated in this is an idea of balanced political democracy in which political parties, based on an active citizenship, let an autonomous space to civil society and state.
Keywords: political party; politične stranke; politologija; politične teorije